2012
DOI: 10.1007/s10544-011-9626-3
|View full text |Cite
|
Sign up to set email alerts
|

Methylene diphosphonate-conjugated adriamycin liposomes: preparation, characteristics, and targeted therapy for osteosarcomas in vitro and in vivo

Abstract: Methylenediphosphonate (MDP)-conjugated adriamycin liposomes (MDP-LADMs) were prepared using mild dynamic dialysis equilibrium method, and their targeted therapeutic effects against osteosarcomas and metastatic SOSP-M lung nodules were evaluated in vivo. The drug loading and encapsulation efficiency of the MDP-LADMs were measured via high-performance liquid chromatography, and their size and morphology of the MDP-LADMs were determined using transmission electron microscopy and a particle size analyzer, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…For the toxicity of DOX, various studies have reported that the LD 50 values of DOX can increase by twofold after loading DOX into nanocarriers. Our group previously reported on methylene diphosphonateconjugated adriamycin liposomes, and Liao et al prepared a targeting liposomal for DOX delivery inhibiting tumor growth without systemic toxicity [45,46] and determined the low toxicity of DOX loaded into nanocarriers. Similar results were found for ApoG2 and AASt MCs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For the toxicity of DOX, various studies have reported that the LD 50 values of DOX can increase by twofold after loading DOX into nanocarriers. Our group previously reported on methylene diphosphonateconjugated adriamycin liposomes, and Liao et al prepared a targeting liposomal for DOX delivery inhibiting tumor growth without systemic toxicity [45,46] and determined the low toxicity of DOX loaded into nanocarriers. Similar results were found for ApoG2 and AASt MCs (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Liposomal encapsulation of doxorubicin has been shown to be effective in vitro and in vivo [159,160]. Furthermore, the efficacy of SLIT cisplatin has been investigated, in particular in osteosarcoma patients [67].…”
Section: Emerging Therapies and New Therapeutic Targetsmentioning
confidence: 99%
“…Additionally, liposomes modified by folic acid actively targeted over‐expressed folate receptor α on the surface of osteosarcoma, indicating that curcumin–C6 ceramide liposomes have an inhibiting effect on osteosarcoma in vivo and in vitro . Wu and Wan performed a similar experiment in which doxorubicin was sealed in a lipid bilayer of liposomes and diphosphonic acid and found that this system had less systemic toxicity and stronger selectivity for osteosarcoma than a bone‐target drug delivery system with a single mechanism. Low et al .…”
Section: Use Of Bone‐targeted Drug Delivery Systems In Neoadjuvant Chmentioning
confidence: 99%